Cytochrome P450 reaction phenotyping and inhibition and induction studies of pinostrobin in human liver microsomes and hepatocytes. (22nd January 2017) - Tan, Shengnan; Dong, Zhimin; Zhang, Jiashuo; Efferth, Thomas; Fu, Yujie; Hua, Xin
Abstract: Pinostrobin (PI, 5‐hydroxy‐7‐methoxyflavanone) is a natural flavonoid known for its rich pharmacological activities. The objective of this study was to identify the human liver cytochrome P450 (CYP450) isoenzymes involved in the metabolism of PI. A single hydoxylated metabolite was obtained from PI after an incubation with pooled human liver microsomes (HLMs). The relative contributions of different CYP450s were evaluated using CYP450‐selective inhibitors in HLMs and recombinant human CYP450 enzymes, and the results revealed the major involvement of CYP1A2, CYP2C9 and CYP2E1 in PI metabolism. We also evaluated the ability of PI to inhibit and induce human cytochrome P450 enzymes in vitro . High‐performance liquid chromatography and liquid chromatography–tandem mass spectrometry analytical techniques were used to estimate the enzymatic activities of seven drug‐metabolizing CYP450 isozymes in vitro . In HLMs, PI did not inhibit CYP 1A2, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6 or CYP3A4 (IC50  > 100 μm ). In the induction studies, PI had minimal effects on CYP1A2, CYP2B6and CYP3A4 activity. Based on these results, PI would not be expected to cause clinically significant CYP450 inhibition or induction.